Pengaturan Pidana Tambahan Ganti Kerugian Terhadap Pelaku Kejahatan Satwa yang Dilindungi dalam Pembaharuan Hukum Pidana di Indonesia - Putri, Aretha; Ardiyanto, Syaifullah Yophi; Hidayat, Tengku Arif (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this study is to examine the concept of regulating compensation as an additional criminal penalty for perpetrators of crimes involving protected wildlife in the reform of criminal law in Indonesia. The focus of the issue lies in the addition of criminal penalties, where the orientation of punishment involves both retribution and the rectification of the consequences arising from the crime. The research method used is normative juridical research with a principle-based approach, analyzed descriptively. The results of the study show the importance of adding compensation penalties as an additional punishment for perpetrators of crimes involving protected wildlife, considering that protected wildlife is a national asset with a significant role. This concept is feasible by referring to the application of additional criminal penalties, such as substitute money penalties in corruption cases and criminal penalties for rectifying the impact of environmental crimes. Moreover, the practice of compensation penalties has been implemented in wildlife crime cases in countries like the United States and Canada. The responsibility for compensation is imposed on the convicted individual in accordance with the "polluter pays" principle, where the burden of ecological damage recovery is assigned to the environmental offender. The compensation funds received would then be used directly for corrective actions such as wildlife rehabilitation, as well as preventive measures in the future through conservation efforts.